2022
DOI: 10.18433/jpps32891
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Outcomes of Intravenous Drug Use-Related Infective Endocarditis in Buprenorphine-Treated Patients

Abstract: Purpose: Intravenous drug use (IVDU) is an independent risk factor for infective endocarditis (IE). IVDU-related IE is associated with poor clinical outcomes, such as infection-related and drug abuse-related readmissions and mortality. Critical interventions to treat addiction, such as medication for opioid use disorder (MOUD) with buprenorphine, may prevent these unfavorable outcomes. This study aimed to establish the effectiveness of buprenorphine prescriptions at hospital discharge for patients admitted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Ray et al found no significant difference in length of stay, readmissions, drug use at readmission, or reoperations between groups with and without MOUD [ 16 ]. O’Kane et al showed no statistical difference in all-cause 180-day readmission or mortality when prescribing buprenorphine at discharge [ 12 ]. Traver et al showed no association with the completion of outpatient parenteral antimicrobial therapy [ 20 ].…”
mentioning
confidence: 99%
“…Ray et al found no significant difference in length of stay, readmissions, drug use at readmission, or reoperations between groups with and without MOUD [ 16 ]. O’Kane et al showed no statistical difference in all-cause 180-day readmission or mortality when prescribing buprenorphine at discharge [ 12 ]. Traver et al showed no association with the completion of outpatient parenteral antimicrobial therapy [ 20 ].…”
mentioning
confidence: 99%